Rethinking participation in the Aarhus as European Capital of Culture 2017 project. Issue 3 (27th May 2018) - Jancovich, Leila; Hansen, Louise Ejgod
ABSTRACT: This paper examines the relationship between cultural participation and regional development with reference to the European Capital of Culture in 2017. From the bidding stage, Aarhus 2017 claimed it put "participation" at the heart of its strategic plans, through consultation at roadshows and exhibitions. In addition, it aspired to use culture as a catalyst for development not only in the city of Aarhus but across the region of Central Denmark. This paper, therefore, examines how participation is defined and implemented to address regional development in the Aarhus 2017 process through textual analysis of documentation from Aarhus 2017 and delivery partners as well as over 20 interviews with managers and participants involved in a range of 2017 projects. The paper argues against the common prioritisation of urban and professional cultural institutions and makes the case for decentralised cultural provision that supports both amateurs and professionals through a regional networked structure.